2018
DOI: 10.24843/ejmunud.2018.v07.i10.p19
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Citra Merek, Kualitas Produk Dan Persepsi Harga Terhadap Kepuasan Dan Niat Beli Ulang

Abstract: Repeat intention is one of the important factors for the company. The re-purchase intention of a product arises because the consumer is satisfied with the product purchased previously. One of the keys in creating a buy-back intention is to increase customer satisfaction. This research was conducted in Denpasar City involving 120 respondents. The purposive sampling method is chosen as the method of data collection. Data collection was done by distributing questionnaires containing statements relating to brand i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
1
26

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 4 publications
(4 reference statements)
4
5
1
26
Order By: Relevance
“…In relation to this, Cok-Kis pays attention to the need and request of customer who are looking at Surabaya souvenirs through the "Suroboyoan" concept, the Suroboyoan concept is displayed by Cok-Kis's dry cookies products that at its base has clover leaf mix, while maintaining texture, aroma, taste qualities and other organoleptic aspects that will ensure customer satisfaction. The result of this research supports previous studies by [10] and [11] who concluded that customer satisfaction has a significant impact on customers repurchase intention.…”
Section: The Effect Of Customer Satisfaction On Repurchase Intentionsupporting
confidence: 90%
See 2 more Smart Citations
“…In relation to this, Cok-Kis pays attention to the need and request of customer who are looking at Surabaya souvenirs through the "Suroboyoan" concept, the Suroboyoan concept is displayed by Cok-Kis's dry cookies products that at its base has clover leaf mix, while maintaining texture, aroma, taste qualities and other organoleptic aspects that will ensure customer satisfaction. The result of this research supports previous studies by [10] and [11] who concluded that customer satisfaction has a significant impact on customers repurchase intention.…”
Section: The Effect Of Customer Satisfaction On Repurchase Intentionsupporting
confidence: 90%
“…The PLS analysis result concludes that Hypothesis 5 (customer satisfaction significantly mediates product quality on repurchase intention of Cok-Kis's customers). This research supports studies by [12], [11], and [16] who in general concluded that product quality will affect on satisfaction and therefore directly affect on the push for customer to repurchase.…”
Section: The Effect Of Mediating Variable Of Customer Satisfaction Onsupporting
confidence: 90%
See 1 more Smart Citation
“…Hasil penelitian yang dilakukan oleh Ida Ayu Putu Dian Savitri dan I Made Wardana dalam (Savitri & Wardana, 2018) ditemukan bahwa citra merek, kualitas produk dan persepsi harga berpengaruh positif dan signifikan terhadap kepuasan pelanggan. Citra merek merupakan variabel yang paling dominan berpengaruh terhadap kepuasan pelanggan.…”
Section: Jenis Penelitianunclassified
“…Kepuasan pelanggan juga memiliki pengaruh positif dan signifikan terhadap niat beli ulang. Sehingga dapat disimpulkan bahwa menciptakan niat beli ulang pada konsumen dapat dilakukan dengan meningkatkan kepuasan pelanggan (Savitri & Wardana, 2018).…”
Section: Jenis Penelitianunclassified